Melawan Amnesia Historis: Mewarisi Sejarah, Membangun Peradaban - Wijayanti, Ratna Nur; Asbari, Masduki; Cahyaningsih, Najwa Dias (AGUSPATI RESEARCH INSTITUTA, 2025)
This research aims to explore the historical and cultural values of Tanah Jawa in the 18th and 19th centuries in the context of the phenomenon of historical amnesia among the younger generation. This research uses a descriptive qualitative approach with a listening-recording technique, in which secondary data is obtained from Peter Carey's oral narration in Gita Wirjawan's YouTube channel entitled “Tanah Jawa 300 Years ago”. The analysis results show that figures such as Prince Diponegoro and Roekmini, as well as the palace cultural system, have strategic roles in forming national identity and strengthening Indonesia's soft power. The phenomenon of historical amnesia that obscures the understanding of history is the starting point of the discussion. This research confirms the importance of revitalizing history through popular media and cultural education as a strategy for future cultural management.